2019
DOI: 10.4314/sajas.v49i3.7
|View full text |Cite
|
Sign up to set email alerts
|

Physical and mechanical characteristics of Hisex Brown hen eggs from three different housing systems

Abstract: The aim of this study was to compare physical and mechanical characteristics of Hisex hen eggs collected from three different housing systems: enriched cage housing, aviary housing, and free-range systems. The following physical and mechanical characteristics if eggs were compared: dimensions, surface area, volume, sphericity, shape index, shell thickness, weight, composition, yolk to albumen ratio, rupture force, specific deformation, absorbed energy, and firmness. The largest and heaviest eggs were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 25 publications
1
9
0
4
Order By: Relevance
“…The albumen percentage was the highest in eggs from conventional system (P <0.01), in accordance with Galic et al (2019). According to Castellini et al (2006), albumen deposition is greatly affected by the level of dietary protein.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…The albumen percentage was the highest in eggs from conventional system (P <0.01), in accordance with Galic et al (2019). According to Castellini et al (2006), albumen deposition is greatly affected by the level of dietary protein.…”
Section: Resultssupporting
confidence: 71%
“…The present results agree with those of Rizzi and Marangon (2012), who observed a negative correlation between yolk to albumen ratio and egg weight. Galic et al (2019) found egg weight was highly correlated with albumen weight. The shell constituted a smaller (P <0.05) percentage of egg weight for hens in CON than those in the FR and ORG systems.…”
Section: Resultsmentioning
confidence: 83%
“…The housing system can affect egg quality in commercial laying flocks. Galic et al. (2019) decided that the housing system of laying hens has a significant effect on egg quality.…”
Section: Discussionmentioning
confidence: 99%
“…Englmaierová et al [60] found that housing technologies significantly influenced egg weight, and while eggs produced in aviary and enriched cage systems had higher average weights, eggs originating from barn housing systems had lower weights. Galic et al [61] reported the same result, i.e., the largest and heaviest eggs were produced in enriched cage systems. Perić et al [54] compared eggs from traditional caged systems, omega-3-enriched eggs and eggs from free-range housing in terms of their external and internal properties which affect egg quality, using samples from one of the largest supermarkets.…”
Section: Egg Quality Issuesmentioning
confidence: 55%
“…In addition, in the examined sample, the yolk of free-range eggs had the lightest color, which is a finding completely opposite to consumer expectations [62]. According to other research [61,63], free-range eggs and their yolks were heavier in weight and the latter was more intensely colored, while the shell of eggs produced in caged housing systems was thicker. At the same time, other indicators of egg quality (e.g., protein and shell weight, protein and yolk pH) were not affected by the given housing technology [63].…”
Section: Egg Quality Issuesmentioning
confidence: 76%